2021
DOI: 10.1111/1467-9566.13288
|View full text |Cite
|
Sign up to set email alerts
|

Narrative reconstruction of mental illness as a work‐stress‐induced disorder: Processes, consequences and implications

Abstract: Stress‐induced mental illnesses have become the focus of increasing international attention, particularly in Japan since the 1990s, where judiciary cases and welfare‐state initiatives established causal links between work stress and mental illness. However, how individuals retrospectively construct this causality remains a marginal topic in the literature. This ethnographic article explores the ways in which male workers seeking compensation for their condition (depression and adjustment disorder) reconstruct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Some explanations involve the negotiation of normality (Korhonen & Komulainen, 2019) and responsibility, or 'blame' (Kangas, 2001;Shimizu, 2021) and can be placed on either an 'internal' or an 'external' axis (Danielsson et al, 2009;Kangas, 2001). Danielsson et al (2009) studied the narratives of depression among primary care patients with clinical depression and found that while internalising explanations focused on self-blaming, externalising explanations presented the aetiological factors outside the body (Danielsson et al, 2009).…”
Section: Illness Narrative Approach To Common Mental Health-related S...mentioning
confidence: 99%
See 3 more Smart Citations
“…Some explanations involve the negotiation of normality (Korhonen & Komulainen, 2019) and responsibility, or 'blame' (Kangas, 2001;Shimizu, 2021) and can be placed on either an 'internal' or an 'external' axis (Danielsson et al, 2009;Kangas, 2001). Danielsson et al (2009) studied the narratives of depression among primary care patients with clinical depression and found that while internalising explanations focused on self-blaming, externalising explanations presented the aetiological factors outside the body (Danielsson et al, 2009).…”
Section: Illness Narrative Approach To Common Mental Health-related S...mentioning
confidence: 99%
“…Danielsson et al (2009) studied the narratives of depression among primary care patients with clinical depression and found that while internalising explanations focused on self-blaming, externalising explanations presented the aetiological factors outside the body (Danielsson et al, 2009). Applying the theory of narrative reconstruction (Williams, 1984), Shimizu (2021) identified three work-related explanations for the aetiology of mental health problems among male workers: objectivising stressful events as psychological symptoms, non-faulting of the self, emphasising work stress as an unavoidable occurrence and negotiating blame with reference to individual causes. In Kangas' (2001) study of lay narratives of depression, internal and external causes were discussed in terms of responsibility.…”
Section: Illness Narrative Approach To Common Mental Health-related S...mentioning
confidence: 99%
See 2 more Smart Citations
“…The negative impacts of job stress on job performance are well documented. In addition, stress can also trigger physical ailments such as headaches, hypertension, and muscle tension, as well as emotional problems such as mood swings, irritability, and disorientation, among others [13].…”
Section: Introductionmentioning
confidence: 99%